ECOART THROUGH VARIOUS APPROACHES - Martinus Dwi Marianto; martinus dwi marianto (Journal of Urban Society's Arts, 2020)
This research was done as an effort to observe, write, and publicize  eco-activism and achievements by a number of eco-actors in the midst of an increasingly natural environmental crisis, to be used as stimuli and teaching materials for the course of  EcoArt. A number of artists practicing ecoartivism were purposively selected as a sample; their works and achievements are exposed. They are Endar Progresto, Widya Purwoko, Bernadeta Pudiasminarsih (Dyas Ecoprint), and Nasirun. These eco-activists not only work ecologically real, but also creatively communicate ecological values to surrounding communities to change. Nevertheless campaigning this environmental crisis for the better cannot be done partially, but must be jointly supported, organized and socialised continuously. For this reason, their works and achievements, as well as their individual ecoartivism need to be exposed, documented, and assembled as one unit as part of selected subjects of the EcoArt Course in the Fine Arts Department of the Indonesia Institute of the Arts Yogyakarta, to generate  enthusiasm in articulating or representing ecological concerns for ecosystem sustainability and preservation of natural environment through Art.